2010
DOI: 10.1172/jci42672
|View full text |Cite
|
Sign up to set email alerts
|

An alphavirus vector overcomes the presence of neutralizing antibodies and elevated numbers of Tregs to induce immune responses in humans with advanced cancer

Abstract: Therapeutic anticancer vaccines are designed to boost patients' immune responses to tumors. One approach is to use a viral vector to deliver antigen to in situ DCs, which then activate tumor-specific T cell and antibody responses. However, vector-specific neutralizing antibodies and suppressive cell populations such as Tregs remain great challenges to the efficacy of this approach. We report here that an alphavirus vector, packaged in virus-like replicon particles (VRP) and capable of efficiently infecting DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
98
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 28 publications
2
98
1
1
Order By: Relevance
“…Our use of a clinically relevant animal model that closely resembles human HCCs warrants interest from a translational research perspective. Although both the long-term and short-term expression vectors that we used in this study showed similar effects, the latter has some intrinsic advantages that could favor its clinical use: (i) alphaviral vectors can be produced at high titers and have been tested in clinical trials, showing a high degree of safety (Bernstein et al, 2009;Morse et al, 2010); (ii) phase I clinical trials have proven the feasibility and low toxicity of intratumoral injection of viral vectors into HCC nodules (Sangro et al, 2004(Sangro et al, , 2010Penuelas et al, 2005); (iii) short-term IL-12 and IFN-c expression was sufficient to achieve potent therapeutic effects, which could reduce the toxicity associated with the long-term expression of these cytokines; and finally, (iv) although improbable, a long-term expressing DNA vector such as pTonL2(T)-mIL12 could integrate into the genome of healthy liver cells, while the RNA SFV-IL-12 vector would quickly disappear because of the apoptosis of infected cells concomitant with tumor regression. All of these properties, together with the high antitumoral efficacy already observed in other clinically relevant models of spontaneous HCC (Rodriguez-Madoz et al, 2009), indicate that SFV-IL-12 could be clinically useful.…”
Section: Discussionmentioning
confidence: 80%
“…Our use of a clinically relevant animal model that closely resembles human HCCs warrants interest from a translational research perspective. Although both the long-term and short-term expression vectors that we used in this study showed similar effects, the latter has some intrinsic advantages that could favor its clinical use: (i) alphaviral vectors can be produced at high titers and have been tested in clinical trials, showing a high degree of safety (Bernstein et al, 2009;Morse et al, 2010); (ii) phase I clinical trials have proven the feasibility and low toxicity of intratumoral injection of viral vectors into HCC nodules (Sangro et al, 2004(Sangro et al, , 2010Penuelas et al, 2005); (iii) short-term IL-12 and IFN-c expression was sufficient to achieve potent therapeutic effects, which could reduce the toxicity associated with the long-term expression of these cytokines; and finally, (iv) although improbable, a long-term expressing DNA vector such as pTonL2(T)-mIL12 could integrate into the genome of healthy liver cells, while the RNA SFV-IL-12 vector would quickly disappear because of the apoptosis of infected cells concomitant with tumor regression. All of these properties, together with the high antitumoral efficacy already observed in other clinically relevant models of spontaneous HCC (Rodriguez-Madoz et al, 2009), indicate that SFV-IL-12 could be clinically useful.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, in a cancer immunotherapy clinical trial comparing two dose levels of a carcinoembryonic antigen (CEA) VRP vaccine, after a single dose of vaccine the anti-vector antibody titer increased dramatically and remained elevated throughout the period of repeated immunizations. Despite this, there was a significant increase in immune response for at least one postvaccination time point versus prevaccination for all three assays (anti-CEA antibody, IFN-␥ ELISpot, and ICS) in the high-dose cohort (13).…”
Section: Discussionmentioning
confidence: 83%
“…These alphavirus-based replicons have been shown to provide robust antigen expression and elicit strong immune responses (Ljungberg and Liljestrom, 2015). Clinical trials have been reported using alphavirus replicon particles as vaccines against infectious diseases such as HIV-1 and CMV, as well as cancers such as prostate and colorectal carcinoma (Bernstein et al, 2009;Morse et al, 2010;Slovin et al, 2013;Wecker et al, 2012). Results of these trials have demonstrated that alphavirus replicon vaccines are safe and immunogenic, generating both antibody and T cell responses (Bernstein et al, 2009;Morse et al, 2010).…”
Section: Introductionmentioning
confidence: 99%